KONTRIBUSI KOORDINASI MATA TANGAN DAN KELENTURAN PERGELANGAN TANGAN TERHADAP KEMAMPUAN PASSING ATAS DALAM PERMAINAN BOLA VOLI SISWA PUTRA SMP NEGERI 15 PEKANBARU - Wijayanti, Ni Putu Nita; ', Anugerah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is still a lack of passing ability on the volleyball games male student SMP 15 Pekanbaru.It is alleged lack of hand-eye coordination and flexibility of the wrist at the time of passing on.The purpose of this research to determine the contribution of hand-eye coordination and flexibility of the wrist to the top passing ability in the game of volleyball,This research is the correlation that aims to determine the relationship between independent and dependent variables.After that, the data normality test with Liliefors test with significance level Î± = 0.05, and gained normality test results X1, Lomax (0.1709) <Ltabel(0,242) and X2 Lomax (0.1646) <Ltabel (0,242) test normality variable Y, Lomax (0.162) <Ltabel (0,242),in other words the normal distribution of data. Then proceed to determine r by using product moment correlation analysis, if rhitung>rtabel then there is a significant relationship,the results showed no significant correlation between hand-eye coordination and flexibility of the wrist against passing ability on volleyball. rhitung (0.54)>rtabel (0.576),thus the conclusion there is no significant correlation between hand-eye coordination and flexibility of the wrist against passing ability on the volleyball games male student SMP 15 Pekanbaru.Based on the analysis can be explained that the results of this research show that there is no positive contribution between hand-eye coordination and flexibility of the wrist against passing on.But if the terms of its contribution variables X1, X2 to Y still has a contribution of 0.49% while 29.16% are influenced by other factors.Key Words:hand-eye coordination, flexibility of the wrist, upper passing ability.